Traditional Healthcare Branding and Marketing Strategies in Hospitals: Efforts to Increase Public Acceptance and Trust Through Innovative Integration - Setya Haksama; Muhammad Chairul Ramadhan; Muhammad Anas (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2026)
Traditional health services in hospitals are concerned with care and treatment that follows prevailing social norms and are safe and effective, using medicines and techniques derived from inherited experience and abilities. These services can be integrated and complemented with existing healthcare services. But it is not that easy to introduce these new innovations to the public. The need to increase public acceptance and trust through this innovative integration. Private hospitals and the government need to implement branding and marketing strategies for traditional health services in hospitals. The purpose of this study is to analyze the branding and marketing strategies of traditional healthcare services in hospitals: efforts to increase public acceptance and trust through innovative integration. This research method is descriptive qualitative research which is a type of qualitative research that aims to describe or describe the phenomenon that is being researched in depth. There are several branding and marketing strategies for traditional health services in hospitals, including marketing with digital technology such as making videos or content about traditional health services. Another strategy is to combine 4P marketing, which is to understand the target market, patients seeking traditional medicine, and their needs. Building trust through educational content, patient testimonials, and a good reputation also needs to be done so that the public trusts and accepts through innovative integration.